How Adults Learn about Multicultural Diversity through Participating in the Arts - Sherre Wesley (Adult Education Research Conference, 2006)
This paper explores the ways in which participating in the arts – through creating, attending or organizing – helps adults learn about multicultural diversity. Learning methods, environments, and key experiences are discussed.
Keywords: Arts participation; multicultural diversity; learning from experience